Integrating Ethics and Corporate Governance for Organizational Performance Across Industries - Fitriani, Wahida; Rosita, Rosita; Annisa, Nahdatul (Journal Development Manecos, 2024)
In this research, authors aim at analyzing the connection between ethics and corporate governance and their consequences regarding organizational performance. Quantitative data was gathered from 150 firms from different industries, and pre-modeled tests such as Pearson correlation, regression analysis, and ANOVA were employed. It is clear that a relationship exists between Ethics and Corporate Governance as there is a positive correlation coefficient of 0.72 which is significant at 0.001. Taking the results of regression analysis into consideration, it is possible to state that out of the two factors considered, ethics has a slightly higher impact on the level of performance (β = 0.55, p - 0.001) than corporate governance (β = 0.45, p - 0.001), which proves the importance of ethical leadership in managing organizational performance. The ANOVA study also pointed to the fact that there were measurable differences in governance between the industries the companies belonged to (F = 4.35, sig < 0.05) with the manufacturing and to some extent finance industries having better governance mechanisms than service industry firms. The paper makes a contribution to the knowledge by filling some of the existing gaps; for example the inability to produce empirical evidence on the effect of ethics on governance and performance as well as the cross-sectional comparator analysis on the varying governing practices in different sectors. It also emphasizes the need to consider ESG factors as a key consideration in corporate governance structures. Thus, the presented results point out the necessity to address the ethical problem as a key characteristic of governance alongside with the analyses of the organisations’ sustainability and the development of strategies to increase the stakeholders’ trust.